Cerebral hemodynamics of the aging brain: risk of Alzheimer disease and benefit of aerobic exercise - Tarumi, Takashi; Zhang, Rong (Frontiers in Physiology, 2014)
Alzheimer disease (AD) and cerebrovascular disease often coexist with advanced age. Mounting evidence indicates that the presence of vascular disease and its risk factors increase the risk of AD, suggesting a potential overlap of the underlying pathophysiological mechanisms. In particular, atherosclerosis, endothelial dysfunction, and stiffening of central elastic arteries have been shown to associate with AD. Currently, there are no effective treatments for the cure and prevention of AD. Vascular risk factors are modifiable via either pharmacological or lifestyle intervention. In this regard, habitual aerobic exercise is increasingly recognized for its benefits on brain structure and cognitive function. Considering the well-established benefits of regular aerobic exercise on vascular health, exercise-related improvements in brain structure and cognitive function may be mediated by vascular adaptations. In this review, we will present the current evidence for the physiological mechanisms by which vascular health alters the structural and functional integrity of the aging brain and how improvements in vascular health, via regular aerobic exercise, potentially benefits cognitive function.